Deletion Mapping and Orientation of the Histidine Operon of Escherichia coli on a Transducing Bacteriophage - Avitabile, Alessandra (1973)
The defective prophage φ80iλc(I)857dhis has been mapped through both marker rescue and deletion analysis. Deletions have been isolated which put residual his genes close to trp genes. Analysis of these deletions shows that the histidine operon on the prophage is oriented clockwise as on the bacterial chromosome, thus opposite to the orientation of the trp operon. The presence of the his promoter-operator region is inferred by the ability of the prophage-carrying strain to derepress sequentially under conditions in which the histidine concentration is limiting. In addition to his, the gnd gene is also present on the prophage and is located between his and trp operons. The bacterial genes are inserted in the right arm of the prophage and substitute for all of the late function genes, except for the first three. These data indicate that the “sense” strand for transcription of the his operon in vivo must be the “R” strand.